Persepsi Remaja Putri tentang Peran Remaja dalam Upaya Pencegahan dan Penanganan Stunting - Imelda Rosniyati Dewi; Eufrasia Prinata Padeng; Reineldis Elsidianastika Trisnawati; Kristina Karisma Harut (Universitas Malahayati Lampung, 2026)
ABSTRACT Programs that involve the participation of adolescent girls have not been followed by a significant decline in cases of anemia in adolescent girls, teenage pregnancy and stunting. Approaches through in-depth interviews can explore the extent of understanding of adolescents as agents of change and human resources who play an important role in family planning and stunting prevention. The purpose of this study was to explore information about the perceptions of adolescent girls about the role of adolescents in preventing and handling stunting. The method used is qualitative with the number of participants three people through in-depth interviews with triangulation of sources of midwives, teachers and ambassadors of planning generation The results of this study illustrate that schoolgirls do not understand all programs involving adolescent girls. Girls' knowledge about stunting must be balanced with compliance, evaluation and comprehensive socialization related to a series of programs involving the role of adolescent girls. Keywords: Perception, Adolescent Girls, Role, Stunting. ABSTRAK Program-program yang melibatkan keikutsertaan remaja putri belum diikuti dengan menurun signifikannya kasus anemia pada remaja putri, kehamilan remaja dan stunting. Pendekatan melalui wawancara mendalam dapat menggali sejauh mana pemahaman remaja sebagai agen perubahan dan SDM yang berperan penting dalam perencanaan keluarga dan pencegahan stunting. Tujuan dari penelitian ini adalah untuk mendalami informasi tentang persepsi remaja putri tentang peran remaja dalam pencegahan dan penanganan stunting. Metode yang digunakan adalah kualitataif dengan jumlah partisipan tiga orang melalui wawancara mendalam dengan triangulasi sumber bidan, guru dan duta generasi berencana. Hasil penelitian ini menggambarkan bahwa siswi belum memahami semua program yang melibatkan remaja putri. Pengetahuan siswi tentang stunting harus diimbangi dengan kepatuhan, evaluasi dan sosialisasi secara komprehensif terkait serangkaian program yang melibatkan peran remaja putri Kata Kunci: Persepsi, Remaja Putri, Peran, Stunting.